Literary archives around the world: the view from Namibia. Issue 1 (November 2018) - Kauaria, Veno V.; Sutton, David
Abstract : This essay draws upon the experience of Namibia as a country which has begun to collect literary archives in the last few years, and which in the course of that new development conducted a survey of collecting practices in many other countries. The essay discusses some of the findings which were specific to Namibia, but principally presents a review of the very different practices and traditions in collecting literary manuscripts which apply in countries around the world.